COMPARATIVE COOPERATIVE LEARNING MODEL OF JIGSAW II TYPE AND NHT TYPE IN SOCIAL ARITHMETIC LEARNING AT GRADE VII STUDENTS OF SMP NEGERI I MAKASSAR - Ruslan Ruslan (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2013)
This research is quasi experiment which is aimed to know whether there is difference of learning result of social arithmetic of students taught by cooperative learning model type Jigsaw II and result of learning of social arithmetic of student taught by using cooperative learning model of NHT type on Students of Class VII of SMP Negeri I Makassar. The result of the research shows that: (1) the learning result of the students taught by using cooperative learning type Jigsaw II model reaches 100% learning completeness, the students get the value with the average score of 84.67, (2) the students' learning result which is taught by using the model NHT type cooperative learning reaches completeness 100% of students get grades with an average score of 78.67, (3) student activity both taught using cooperative learning model type Jigsaw II even NHT during meetings in a certain time is effective, (4) Cooperative students on both cooperative types used in effective learning, and (5) student responses to positive learning. Likewise, the results of inferential statistical analysis indicate that there are significant differences between the scores of student learning outcomes taught by cooperative learning model type Jigsaw II and score of student learning outcomes are taught with NHT type for social arithmetic subject, so from the results of this study can be concluded that the model Cooperative learning type jigsaw II and type of NHT differ significantly, and can be used as one of the learning model that can improve student learning outcomes, especially for the material of arithmetic of socio-students at grade VII SMP and equal